Asymmetric Synthesis, Characterization and Stereoselectivity of Novel 1-2-[(1R,2S)-2-(Chloromethyl)cyclopropyl]ethyl-4-methoxybenzene via Boronate Complex - Hussain, Habib; Rubina Gilani, Syeda; Ali, Zulfiqar; Hussain, Imdad (Asian Journal of Chemistry, 2014)
Novel 1-[2-(1R,2S)-2-(chloromethyl)cyclopropyl]ethyl-4-methoxybenzene was synthesized by cyclopropanation reaction through a novel route. Carbamate was reacted with 2-allyl-4,4,5,5-tetramethyl-1,3,2-dioxaborolane to form boronic ester which was further treated with 1-bromo-3,5-bis(trifluoromethyl)benzene in the presence of n-BuLi and nucleophilic boronate complex was synthesized. 1-[2-(1R,2S)-2-(chloromethyl)cyclopropyl]ethyl-4-methoxybenzene was then prepared by reacting boronate complex with different electrophiles like trichloroisocyanuric acid (TCCA) and N-chlorosuccinimide (NCS). Yields and diastereomeric ratios (d.r) were studied by using various aryl lithiums and electrophiles at different temperatures. Best yield, diastereomeric ratio (d.r), enantiomeric ratio (e.r), enantiomeric excess (e.e), enantiospecificity and [a]D were 67 %, 2.1:1, 68.6:28.9, 39.7, 0.41 and +3.84, respectively.